Effect of Chlorhexidine and Castor Oil on Surface Roughness of Heat-Cured Acrylic Resin Denture Base - Gaol, Elkana Lumban; Utami Ritonga, Putri Welda (Dentistry Faculty, 2023)
Background: Heat-cured acrylic resin is the acrylic resin most often used to make denture bases. In its use as a denture base, heat-cured acrylic resin requires a disinfectant to clean it from contamination by microorganisms. Still, it does not affect other properties of the heat-cured acrylic resin. Objective: This study aimed to determine the effect of heat-cured acrylic resin denture base disinfection with chlorhexidine and castor oil on surface roughness. Materials and Methods: This research is laboratory experimental with 30 bar-shaped (50x20x3mm) heat-cured acrylic resin-denture base specimens samples were divided into two groups, with chlorhexidine 0.2% simulated 3, 4, and 5 years and with castor oil 10% affected 3, 4, and 5 years. The surface roughness was tested using the Roughness tester TR200. Data were analyzed using univariate statistics and an independent t-test ( = 0.05). Results: The research showed no significant effect in the disinfection of heat-cured acrylic resin denture base with 0.2% chlorhexidine and 10% castor oil on surface roughness of 3, 4, and 5 years (p 0.05). Castor oil of 10% can be used as a disinfectant for the heat-cured acrylic resin denture base because it does not affect the surface roughness. Conclusion: Chlorhexidine 0.2% and castor oil 10% had the same effect on changes in surface roughness on heat polymerized acrylic resin denture base.